Peran pemahaman makna bahasa Arab dalam memperkuat daya ingat hafalan Al-Qur’an - Adzkia Maulida, Siti Nur (Maliki Interdisciplinary Journal, 2026)
Understanding the meaning of Arabic plays an important role in the process of memorizing the Qur’an, especially amid the rise of tahfidz methods that focus on repetition without deep comprehension. A lack of understanding of Arabic vocabulary and structure often causes memorization to be easily forgotten, difficult to organize logically, and requires longer time for revision (muraja’ah). This study examines how understanding the meaning of Arabic can strengthen the memorization retention of the Qur’an. Using a literature review method, this research analyzes journals and academic sources discussing the relationship between language, cognition, and memorization ability. The results show that memorizers who understand the meaning of the verses are better able to connect each part conceptually, thereby reducing memorization errors, increasing focus, and accelerating the revision process. In addition, understanding nahwu, sharaf, and the grammatical patterns of the Qur’an helps create a stronger memorization structure. To support the effectiveness of tahfidz, it is necessary to integrate systematic Arabic learning into memorization programs, so that memorizers do not only recall the text but also understand the message contained within it.